ATTITUDE OF PATIENTS TOWARDS ORAL HYGIENE DURING ORTHODONTIC TREATMENT - PRIYA RANJINI; DR.R.NAVANEETHAN M.D.S (International Journal of Pharma and Bio Sciences, 2016)
A study was performed to assess the attitude of the Orthodontic patients towards maintenance of oral hygiene. A questionnaire was put forth to 100 patients who were undergoing Orthodontic therapy to evaluate the oral hygiene aid they used. The patient’s oral hygiene practices before starting Orthodontic therapy had been compared with the oral hygiene measures taken during orthodontic therapy to see if they have increased their efforts at maintaining oral hygiene during orthodontic treatment. Results showed that though there was a significant improvement in most of the patients, there were still a group of patients who have taken no additional efforts to improve on their oral hygiene practices.